Text complexity analysis of college English textbooks based on blockchain and deep learning algorithms under the internet of things. (15th May 2023) - Shen, Bingjie
College English textbooks are of great significance in college English teaching. In the context of the gradual development of the Internet of Things (IoT), this study introduces blockchain and deep learning to build a new college textbooks-oriented complexity analysis model. Three different college English textbooks are analysed from the perspectives of lexical complexity, grammatical difficulty, sentence coherence and sentence readability to ensure the comprehensiveness of the experiment. This study focuses on the text of the textbook, introduces vocabulary research into the system, and takes it as an indicator to judge the textbook. The results can provide suggestions and improvement directions for the subsequent editing and writing of college English textbooks.